THE EFFECT OF HEALTH EDUCATION ON SELF-EFFICACY OF COVID-19 BOOSTER VACCINATION IN PALEMBANG - Agus Submit (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2024)
Background: The national vaccination program has reached 95% dose 1 and 80% dose 2, however the policy for follow-up vaccination (booster) coverage is still very low, only reaching 14%. This affects, among other things, public knowledge about the Covid-19 booster vaccination, which is still low, which has an impact on people's self-efficacy regarding the Covid-19 booster vaccine. Health education can increase the self-efficacy of the Covid-19 booster vaccine. Objective: This study aims to determine the effect of health education on the self-efficacy of the Covid-19 booster vaccine. Method: This research is a pre-experimental research, with a one group pretest-posttest design planning approach. The number of samples in this research was 30 respondents using a consecutive sampling technique. The instrument used to measure self-efficacy in this research is the Self efficacy Questionnaire. Results: The average self-efficacy of the Covid-19 booster vaccine before health education was 36.67 and after health education was 46 with a p-value of 0.001 (p value < 0,05). Conclusion: This shows that there is a significant influence between health education on the self-efficacy of the Covid booster vaccine -19.